Spiritualitas Masyarakat dalam Menghadapi Musibah Banjir: Dinamika Respons Emosional dan Religious Coping - Azizah, Nurul; Daulay, Annisa Arrumaisyah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study explores how a community faced the aftermath of a flood, beginning with their emotional turmoil, moving through the religious strategies they embraced, and culminating in their search for spiritual meaning and heightened environmental awareness. Set in Kubu Village, Peusangan Siblah Krueng subdistrict, Bireuen regency, the research, conducted after the flood of 27 November 2025, draws on in-depth interviews, observations, and documentation. Using NVivo 14 Plus, the data was analyzed to uncover key patterns and themes. The findings reveal that as the floodwaters rose, the community was swept by panic, fear, and anxiety. In response, they leaned on religious coping methods like prayer, remembrance of God (dhikr), seeking forgiveness (istighfar), trusting in God (tawakal), and strengthening their faith. These practices became a source of emotional solace amid the turmoil. Through this journey, they gained psychological stability and began to view disasters as both tests and expressions of God’s will. Their experience also sparked a deeper environmental awareness and a stronger commitment to preventing future calamities. The study concludes that the community’s spirituality blossomed gradually after the disaster, shaped by a blend of psychological, religious, and ecological influences. These insights underscore the importance of a holistic approach in supporting communities as they recover from disasters.